Gift-Me : Personalized Gift Recommender System - Taware Shruti; Yadav Krushna; Khatri Pavan (Universitas Lampung, 2018)
Nowadays most of the india market is moving towards an online world with an adroit to have an maximum market scope .So we are connecting the business of gift article to online world with the evolved versions of current algorithm of recommendation systems.Ecommerce is an online site where the sale or purchase of goods are ordered electronically.The available ecommerce system have some issues with the recommendation so we are collaborating the multiple algorithm to increase the product sale and convinient in user interaction